THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, WORK DISCIPLINE, AND WORK ENVIRONMENT FOR THE PERFORMANCE OF LOADING AND UNLOADING EMPLOYEES AT PT. MMP (MOROWALI MITRA PERKASA) CENTRAL SULAWESI - Khrisna, Gagas Pandu; Santoso, Bowo (International Journal of Multidisciplinary Research and Literature, 2024)
This research is entitled The Influence of Organizational Commitment, Work Discipline, and Work Environment for the Performance of Loading and Unloading Employees at PT.MMP (Morowali Mitra Perkasa). Quantitative research is utilized in this approach to research, with employee performance as the dependent variable and organizational commitment, work discipline, and work environment as the independent variables. The population in this study were employees in the field, totaling 530 employees. The sample for this research was determined using a "Probability Sampling" design, explicitly employing the "Simple Random Sampling" method, which involved the application of the Slovin formula calculation. Upon employing calculations utilizing the Slovin formula, it was ascertained that the number of samples deemed representative of the population amounted to 84 respondents. The research analysis technique employed in this study utilizes the partial least squares (PLS) method. The findings derived from the analysis conducted in this research are as follows: 1) Organizational Commitment Influences Employee Performance. 2) Work Discipline Influences Employee Performance. 3) The work environment influences employee performance